2020
DOI: 10.1016/j.scitotenv.2020.138778
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 transmission in Mainland China is associated with temperature and humidity: A time-series analysis

Abstract: Journal Pre-proof J o u r n a l P r e -p r o o f 2 Title: COVID-19 transmission in Mainland China is associated with temperature and humidity: a time-series analysis Abstract COVID-19 has become a pandemic. The influence of meteorological factors on the transmission and spread of COVID-19 is of interest. This study sought to examine the associations of daily average temperature (AT) and relative humidity (ARH) with the daily count of COVID-19 cases in 30 Chinese provinces (in Hubei fromGeneralized Additive Mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
309
6
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(357 citation statements)
references
References 15 publications
31
309
6
11
Order By: Relevance
“…Yet, there is limited agreement on the shape and magnitude of those relationships. While studies find correlations between pandemic severity and variations in temperature (9,(15)(16)(17)(18)(19)(20)(21)(22), relative and absolute humidity (9,(16)(17)(18)(19)(20)(21)(22)(23)(24), ultraviolet light (19), wind speed (18,21), visibility, and precipitation (17), others (19,(25)(26)(27) indicate weaker, inconsistent, or no relationships. A recent review finds inconclusive evidence for the role of weather in COVID-19 transmission (1) and others caution against interpreting weather as a key driver due to this uncertainty (28).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is limited agreement on the shape and magnitude of those relationships. While studies find correlations between pandemic severity and variations in temperature (9,(15)(16)(17)(18)(19)(20)(21)(22), relative and absolute humidity (9,(16)(17)(18)(19)(20)(21)(22)(23)(24), ultraviolet light (19), wind speed (18,21), visibility, and precipitation (17), others (19,(25)(26)(27) indicate weaker, inconsistent, or no relationships. A recent review finds inconclusive evidence for the role of weather in COVID-19 transmission (1) and others caution against interpreting weather as a key driver due to this uncertainty (28).…”
Section: Introductionmentioning
confidence: 99%
“…The average incubation period is 5-6 days with the longest incubation period of 14 days [6,7,8,9,10]. In addition to person-to-person transmission of COVID-19 through direct contact or droplets [11], studies have shown that geographical, and climatic factors are important factors in the transmission and survival of coronaviruses [12,2,13,14,15,16,17] . For example, temperature could increase or decrease the transmission risk by affecting the survival time of coronaviruses on surfaces [18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…in Relative Humiditywas associated with reduced mortality rate by 3.08% and 0.85% reduction of daily new cases of COVID-19 infection. In this study a 1°C increase in temperature leads to a 10% increase in COVID-19 infection rates (Qi et al 2020;Wu et al 2020b…”
mentioning
confidence: 80%
“…There have also been studies relating to COVID-19 infection rates and geo-meteorological parameters. Temperature, humidity, and rainfall may have a direct in uence to spread the COVID-19 and other infectious vector-borne diseases (Casanova et al 2010;Qi et al 2020). (Xie and Zhu 2020) conducted a study in 122 cities across China to establish epidemiological and experimental research on ambient temperature and COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation